Turistični obisk visokogorja na območju Kamniške Bistrice - Cigale, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
The paper discusses characteristics of tourist/leisure visits of mountain summits in high mountain area of Kamniška Bistrica and various factors that influence them. For the analysis of visits, data from summit books were used. Summits differ in number of visitors, their regional origin and their choice of starting points as well as in the extent to which the visitors are climbing more than one summit during the visit.
Keywords: geography of tourism; Kamnik Bistrica; Kamnik–Savinja Alps; Kamniška Bistrica; Kamniško-Savinjske Alpe; mountaineering; planinarjenje; recreation; rekreacija; Slovenia; Slovenija; tourism; turistična geografija; turizem